Assisting persons with communication disabilities to access the criminal justice system: South African legal practitioners' perceptions of questioning strategy guidelines - Bornman, Juan (University of Pretoria, 2023)
Mini Dissertation (MA (Augmentative and Alternative Communication))--University of Pretoria, 2023.